Treatment patterns and outcomes of unfit and elderly patients with Mantle cell lymphoma unfit for standard immunochemotherapy: A UK and Ireland analysis. (7th May 2021) - Rampotas, Alexandros; Wilson, Matthew R.; Lomas, Oliver; Denny, Nicholas; Leary, Heather; Ferguson, Graeme; McKay, Pamela; Ebsworth, Tim; Miller, Jonathan; Shah, Nimish; Martinez‐Calle, Nicolas; Bishton, Mark; et al.
Summary: Mantle cell lymphoma (MCL) presenting in elderly, unfit patients represents a clinical challenge. Front‐line 'attenuated' or low‐intensity immunochemotherapy is often employed, although outcomes are relatively unexplored. We report outcomes of attenuated immunochemotherapy in 95 patients with MCL across 19 centres in the UK and Ireland considered unfit for full‐dose rituximab‐bendamustine or rituximab‐cyclophosphamide, doxorubicin, vincristine, prednisolone (R‐CHOP). Regimens examined were rituximab‐cyclophosphamide, vincristine, prednisolone (R‐CVP) ( n  = 19), dose‐attenuated R‐CHOP ( n  = 22), dose attenuated rituximab‐bendamustine ( n  = 24) and rituximab‐chlorambucil ( n  = 30). The primary outcome was progression‐free survival (PFS). The secondary outcomes included overall response, overall survival (OS) and toxicity. The median (range) age was 79 (58–89) years and 50% were aged ≥80 years. The median (range) Cumulative Illness Rating Scale‐Geriatric score was 6 (0–24). The median PFS for all patients was 15 months [95% confidence interval (CI) 8·7–21·2) and median OS was 31·4 months (95% CI 19·7–43·2). By multivariable analysis (MVA), the only clinical factor associated with an inferior PFS was blastoid morphology [hazard ratio (HR) 2·90, P  = 0·01). Notably, higher treatment intensity (R‐CHOP/R‐bendamustine composite) provided an independently superior PFS compared with R‐CVP/R‐chlorambucil (MVA HR 0·49, P  = 0·02). Factors associated with inferior OS by MVA were Eastern Cooperative Oncology Group Performance Status (HR 2·14, P  = 0·04), blastoid morphology (HR 4·08, P  = 0·001) and progression of disease at <24 months status (HR 5·68, P  < 0·001). Overall, survival after front‐line dose‐attenuated immunochemotherapy is unsatisfactory. Clinical trials investigating novel agents such as Bruton tyrosine kinase and B‐cell lymphoma 2 inhibitors in this specific clinical setting are warranted.